Technological writing interventions in mental health occupational therapy: considerations for ethical and effective practice - Haertl, Kristine (Frontiers in Psychiatry, 2025)
The application of creative and therapeutic writing interventions within mental health occupational therapy remains underexplored in the current literature. Occupational therapists frequently adapt approaches from related disciplines, such as psychology, to develop interventions for individuals with mental health conditions. With the increasing integration of digital tools, including online journals, blogs, and artificial intelligence (AI), there is a growing opportunity to enhance occupational therapy practices through creative and expressive writing. This paper provides a concise review of relevant literature, examines current and emerging uses of creative and therapeutic writing in occupational therapy, and explores key practical and ethical considerations for both therapists and clients.